Biocontrol Potential of Some Rhizospheric Soil Bacterial Strains against Fusarium culmorum and Subsequent Effect on Growth of Two Tunisian Wheat Cultivars - Habiba Kouki; Mouna Souihi; Ilhem Saadouli; Sabrine Balti; Amira Ayed; Nihed Majdoub; Amor Mosbah; Ismail Amri; Yassine Mabrouk (Microorganisms, 2023)
PGPR (Plant Growth Promoting Rhizobacteria) are used as biofertilizers and biological control agents against fungi. The objective of this work was to evaluate the antagonistic activities of some bacterial strains isolated from soil against four phytopathogenic fungal strains (Fusarium graminearum, F. culmorum, Phytophthora sp. and Verticillium dahlia). Two strains having an antagonist effect on fungi and displaying the maximum of plant growth promoting (PGP) traits were selected for further study and identified as Bacillus subtilis and B. amyloliquefaciens respectively. In planta assays demonstrated that the two Bacillus strains are able to enhance plant growth of two wheat cultivars in absence of nitrogen and protect them against F. culmorum. Pot experiments performed in a greenhouse showed that wheat plants inoculation with two bacterial strains reduce F. culmorum disease severity correlated with the accumulation of phenolic compounds and chlorophyll content. These could partly explain the effectiveness of these bacteria in protecting Tunisian durum wheat cultivars against F. culmorum. Application B. amyloliquefaciens, showed better protection than B. subtilis although the last one enhanced more the plant growth of two wheat cultivars in absence of fungus. Hence, combination of two bacterial strains could be a strategic approach to enhance plant growth and control plant diseases.